ANALISIS KESULITAN MEMBACA PADA SISWA KELAS 1 SD 2 KALIWUNGU - Dina Putri Ariyani; F. Shoufika Hilyana; Much Arsyad Fardani (Jurnal Muara Pendidikan, 2023)
Reading difficulties are obstacles in reading experienced by students. The purpose of this study was to analyze the characteristics of student's difficulties in reading. This research uses a qualitative approach. This research will be carried out at SD 2 Kaliwungu with the subject of research, namely five grade 1 students. This study used data collection techniques in the form of observation, interviews, and documentation. The data analysis used is qualitative data analysis with data reduction, data presentation, and conclusion drawing and verification. The results showed that five grade 1 students had difficulty reading, including difficulty recognizing and identifying letters of the alphabet, unable to distinguish letters that are almost similar when reading, difficulty in spelling letters and syllables, difficulty in pronouncing consonant combinations, difficulty in pronouncing diphthong combinations, and difficulty in pronouncing the letter "r". Based on the results of data analysis from several previous studies and various references or sources that there are still low-grade students who have difficulty reading with some characteristics of reading difficulties they experience.